Migration from rural areas; the evidence from village studies - Connel, John. ...[et. al] (Delhi, 1978)
This study is part of a wider analysis of village conditions in the developing world conducted by the Village Studies Programme at the Institute of Development Studies, University of Sussex and financed by a research grant from the ILO. It is the first attempt to bring together the evidence on migration available from numerous intensive village studies carried out in all areas of the Third World, including Latin America and Africa. The book consists of three parts: the authors first consider the sorts of village likely to send out migrants; in the second part they examine the main forms of impact of migrants on the village and its households; the third part consists of a cross-sectional case-study of the results of 40 Indian village surveys, from four Agro-Economic Research Centres, containing roughly comparable data on migrants. The results of this systematic statistical analysis tend strongly to confirm the world-wide. but more 'verbal' and less rigorous, evidence of the first two parts.
Keywords: Migration, Internal